Statistics of Road Traffic Accidents in Europe and North America 2021 - United Nations Economic Commission for Europe (United Nations, 2022)
This publication (volume LVI) presents annual statistics on road traffic accidents and provides comparable data on causes, types, and results of accidents in Europe, Canada, and the United States. Data are organized by nature of accident and surroundings; accidents while under the influence of alcohol; and the number of persons killed or injured, by category or road user and age group. As background data, figures on the number of road vehicles in use and vehicle-kilometers run by road vehicles are also provided along with estimates of population and distribution by age group. This annual publication contains important statistical information for those involved in transportation planning and road safety issues.